Possible role of DMP1 in dentin mineralization - Beniash, Elia (2010)
Dentin Matrix Protein 1 (DMP1), the essential noncollagenous proteins in dentin and bone, is believed to play an important role in the mineralization of these tissues, although the mechanisms of its action are not fully understood. To gain insight into DMP1 functions in dentin mineralization we have performed immunomaping of DMP1 in fully mineralized rat incisors and in vitro calcium phosphate mineralization experiments in the presence of DMP1. DMP1 immunofluorescene was localized in peritubular dentin (PTD) and along the dentin-enamel boundary. In vitro phosphorylated DMP1 induced the formation of parallel arrays of crystallites with their c-axes co-aligned. Such crystalline arrangement is a hallmark of mineralized collagen fibrils of bone and dentin. Interestingly, in DMP1-rich PTD, which lacks collagen fibrils, the crystals are organized in a similar manner. Based on our findings we hypothesize, that in vivo DMP1 controls the mineral organization outside of the collagen fibrils and plays a major role in the mineralization of PTD.